PSYCHOLOGICAL SUPPORT OF ELDERLY PEOPLE IN PANDEMIC PERIOD (features of online webinars support) - Катерина Годлевська; Кирил Котун (Ivan Ziaziun Institute of Pedagogical Education and Adult Education of the NAES of Ukraine, 2021)
The article analyzes the features of technical organization and support of online webinars created for psychological support of the elderly and their families, their testing in social networks and use on the Internet by the target audience. The peculiarities of using the ZOOM platform, AnswerGarden and Padlet services to conduct a series of webinars created within the objectives of the project «Psychological support for the elderly in pandemic period», recommended for implementation in 2020-2021 with grant support by the National Research Foundation of Ukraine. Using online services for a series of webinars allowed participants to save time, as they do not need to spend it on the way to the venue of the webinars; most of the participants were in different cities and regions of Ukraine; Convenience was also important, as webinars participants could be in a convenient place. The results of webinars participant's registration are covered, in particular: age category, type of employment, territorial affiliation. Here is an example of statistics on webinars views on the YouTube channel «Vik Obranyh». It is determined that the advantages of using webinars are: providing information accessible, understandable to anyone, language, taking into account the age characteristics of the elderly, reaching a large audience. The practical value of webinars lies in influencing the emotional, cog-nitive, and behavioral components of the individual's psyche to provide psychological support to older people who are in difficult life circumstances due to forced self-isolation. The social effect of webinars is that the use of the information obtained will help to improve the psychological well-being of older people in conditions of forced self-isolation. Difficulties identified during the webinar cycle were identified. The ways of high-quality provision of webinars organization, attraction of the audience with the help of advertising posts and e-mail mailings are revealed